GB3D – a framework for the bedrock geology of Great Britain. (3rd January 2014) - Mathers, S. J.; Terrington, R. L.; Waters, C. N.; Leslie, A. G.
<x xml:space="preserve">Abstract</x> In 2011, the British Geological Survey (BGS) decided to begin the assembly of a National Geological Model (NGM) from its existing and on‐going geological framework models comprising integrated national crustal, bedrock, and Quaternary models. The bedrock component is the most advanced of these themes and comprises both the calculated models and a complementary network of cross sections that provide a fence diagram for the bedrock geology of Great Britain. This fence diagram, the GB3D_v2012 dataset, is the subject of this article and is available in a variety of formats from the BGS website (www.bgs.ac.uk) as free downloads. It complements the existing 1:625 000 scale map sheets published by BGS utilizing the same colour schema and geological classification. The 121 component cross sections extend to depths between 1.5 and 6 km; they have an aggregate length of over 20 000 km, and they are snapped together at their intersections to ensure total consistency. The sections are guided by the existing BGS geological framework models where they cut through them; they also take account of the vast wealth of published data on the subsurface structure of Britain both from BGS and in the literature. Much of this is in the form of cross sections, contour maps of surfaces, and thicknesses (isopachs). The fence diagram has been built in the Geological Surveying and Investigation in 3D (GSI3D) software. Utilizing the cross sections and the coverages of the geological units simple 3D volumes can be calculated for the less deformed sedimentary strata. It is envisaged that this dataset will form a useful educational resource for geoscience students and the general public, and also provide the bedrock geology context and structure for regional and catchment scale studies.